A novel BIM-based process workflow for building retrofit. (1st June 2022) - D'Angelo, Letizia; Hajdukiewicz, Magdalena; Seri, Federico; Keane, Marcus M.
Abstract: The European Union (EU) has developed policies aimed at accelerating the retrofit of existing buildings, with the vision of a decarbonised building stock by 2050. Retrofitting of existing buildings offers significant opportunities to reduce global energy consumption and greenhouse gas emissions. Although there is a wide range of government incentives available, retrofits only affect 0.5–1% of the building stock per year. Thus, this research conducted a literature review in order to identify the barriers preventing retrofitting of existing buildings. These barriers include low financial availability, user awareness, uncertainty in regulatory frameworks and fragmentation of the supply chain. The research presented here overcomes these retrofit barriers by developing a novel step-by-step guideline for building retrofit. The proposed workflow combines the benefits of Building Information Modelling (BIM) with the Business Process Modelling (BPM) technique. BIM is used for its capacity to create and manage information along the full life-cycle of a building. While BPM allows to optimise the retrofit workflow, by providing all relevant stakeholders with (i) the instruments to better understand their roles and responsibilities in the retrofit process, (ii) the technological framework and data needed to efficiently implement BIM within the project. This novel BIM- BPM workflow was demonstrated on a residential pilot building located in Inis Mór, Ireland. Highlights: A novel BIM and Business Process Modelling (BPM) framework is developed to support the retrofitting of existing buildings. BIM is used to better manage the information along the entire buildings project life-cycle. BPM enables the stakeholders to analyse the workflow, allowing a better communication and identification of project roles. The BIM based retrofit workflow is utilised to evaluate the most cost-effective retrofit measure in a residential house.